Victorian literature : a sourcebook - Vadillo, Ana Parejo; Gagnier, Regenia; Richardson, Angelique; Rylance, Rick; Young, Paul (London ; New York : Palgrave Macmillan, 2012)
This is an anthology of both familiar and previously unavailable primary texts that illuminate the world of 19th-century ideas. An expert team introduce and annotate a range of original social, cultural, political and historical documents necessary for contextualizing key literary texts from the Victorian period.
Includes bibliographical references and index
Keywords: English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century